Evagrius on Sadness - Christie, Douglas E. (Cistercian studies quarterly, 2009)
The article discusses the role of sadness in the spiritual life of Christian. It focuses on the moral and spiritual importance of sadness within the Christian spirituality, centering on the impact of sadness to the life of monks. It also accounts how Christians tend to accept the challenge to morally and spiritually struggle and understand the presence of sadness. In addition, it accounts the work of fourth-century monastic writer Evagrius of Pontus on the function of sadness among Christian.